Contribution of NEO Modernism Thoughts on Islamic Thoughts in Indonesia - Annai Saburi; Hasan Bakti Nasution; Irwansyah Irwansyah (Budapest International Research and Critics University, 2020)
The aim of the study is to find out the contribution of NEO modernism trought on Islamic trough in Indonesia. This result of the study is Islamic Civilization